Caregiver Perspectives on Patient Participation in Biological Pediatric Cancer Research - Nicole E. Kendel; Jennifer A. Belsky; Joseph R. Stanek; Keri A. Streby; Nilay Shah (MDPI AG, 2022)
Adolescent cancer patients and their caregivers have demonstrated willingness to participate in invasive biological sampling, either for their own potential benefit or for research purposes. However, many malignancies occur primarily in prepubescent patients and there are no similar studies in this population. Our study objective was to assess the willingness of caregivers to consent to research studies involving invasive biological sampling in children ≤ 13 years of age. Participants completed a survey assessing their willingness to allow various procedures both with and without clinical benefit to their children. Most respondents were willing to allow additional blood draws regardless of potential benefit to their children (95.6% were willing when there would be benefits and 95.6% were willing when there would not). Although the overall willingness was lower with other hypothetical procedures, the majority of respondents were still willing to allow additional biopsies for research purposes. Caregivers of young children with cancer will allow their children to undergo additional invasive procedures for research purposes. This willingness decreased with more invasive procedures without potential direct benefit, but interest remained in more than half of participants. Caregivers for young patients with cancer should be approached for participation in future biological/correlative studies.